Optimization and Quality Evaluation of Takha: A Nepalese Indigenous Meat Product. - SHERMA, GIRIJA; ACHARYA, DEV RAJ; RAI, KISHOR; KHADKA, NABIN; GURUNG, GAURAV; GIUFFRÈ, ANGELO MARIA; DANGAL, ANISH (Current Research in Nutrition & Food Science, 2026)
Takha, an indigenous Newari meat product, is prepared from low-value cut-off parts of male buffalo (Bubalus bubalis), such as head meat, tail, bones, cartilage, and skin. This study aimed to optimize the proportions of raw materials (skin and bone), cooking time, setting time, and spices mix quantity. An experimental design was developed using Design Expert® v. 6.0.10, based on Response Surface Methodology and a Central Composite Face-Centered Design, incorporating variations in skin content (50–100%), bone content (0–50%), cooking time (2–6 h), and setting time (4–8 h). Following optimization, five Takha samples were prepared with spice mix quantities ranging from 90 to 167 g/kg using mixture design and labeled as A (90.00 g/kg), B (109.25 g/kg), C (128.5 g/kg), D (147.75 g/kg), and E (167 g/kg). Sensory analysis preferred sample A as the optimized product, with a skin-to-bone ratio of 62.27:33.73. It was pressure-cooked for 3.5 h at medium heat using 90 g/kg of spices mix and refrigerated at 8 °C for 4 h. The optimized Takha had 20.85% moisture, 79.15% total solids, 71.12% protein, 4.95% fat, 16.60% ash, 7.33% carbohydrates, 4.5% salt, and a pH of 6.45. Microbiological analysis showed that the product remained fresh for 14 days without preservatives, however, between 14 and 28 days, the total plate count increased excessively, with a coliform level of 2.373×10³ cfu/g.